Homework in Elementary School - Hidayah, Ratna; Salimi, Moh; Suhartono, Suhartono; Susiani, Tri Saptuti; Ngatman, Ngatman Ngatman (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
Education is invesment for the future. The phrase discribed how attractiveness the future with prosperity, a society desirable. But it could not be reached without efforts from anyone who involved in education process. School, family, and society was centered of education. In those institution education held. So, it was plausibility disscuss the cooperation of those institution. Our focus disscuss was homework as medium to cooperate between school and family. The cooperation between one institution with onether for long time means empowering the institution it self. Homework is a time honored practice that can enhance the development of skills and reinforce knowledge gained within the classroom when it used effectively and appropriately. The purposes of homework serve three main functions instructional, communicative, and political. In instructional function, homework is natural extention of the curricular programs because it is an integral component of instruction. It can also serve as a vital link between theschool and family.